1972
DOI: 10.1037/h0032656
|View full text |Cite
|
Sign up to set email alerts
|

Interest patterns of psychologists in nine Western nations.

Abstract: and the Union of South Africa (abbreviated ACGNU countries)-completed the revised Strong Vocational Interest Blank (SVIB) for Men. Their responses and scores were compared with corresponding earlier data from 256 Austrian, German, and Swiss (abbreviated AGS) psychologists, who took the translated SVIB, and with anchoring data from 1,045 United States psychologists tested in 1947. One-way analyses of variance for ACGNU countries on 81 SVIB scales resulted in only 8 significant differences. At the item level, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Several JAP articles during this period did begin to investigate differences in managerial beliefs and values across countries. Notably, Hofstede (1976) published a paper in JAP on values of managers from 40 nationalities, which were organized into five clusters (Nordic, Germanic, Anglo, Latin, and Asian), and Lonner and Adams (1972) described vocational interests across nine nations. Others explicitly stated a need to recruit cross-cultural samples to expand the focus of I/O psychological research.…”
Section: Middle 20th Century (1950-1979)mentioning
confidence: 99%
“…Several JAP articles during this period did begin to investigate differences in managerial beliefs and values across countries. Notably, Hofstede (1976) published a paper in JAP on values of managers from 40 nationalities, which were organized into five clusters (Nordic, Germanic, Anglo, Latin, and Asian), and Lonner and Adams (1972) described vocational interests across nine nations. Others explicitly stated a need to recruit cross-cultural samples to expand the focus of I/O psychological research.…”
Section: Middle 20th Century (1950-1979)mentioning
confidence: 99%
“…Virtually all of the leading journals and textbooks are published in the United States, with a few British contributions making up the rest. In an earlier empirical study, Lonner and Adams (1972) gave the Strong Vocational Interest Test (SVIT) to psychologists in eight countries including Australia. The results were compared with data from 1,045 U.S. psychologists.…”
Section: Australiamentioning
confidence: 99%
“…The SII has been used internationally to examine relative benchmark occupations (e.g., police officers, engineers, and physicians). Studies conducted in Germany, Mexico, Austria, Switzerland, Scotland, Australia, Canada, Great Britain, New Zealand, South Africa, and Pakistan showed that people within an occupation were more similar across countries than individuals in the same country across occupations (Fouad & Hansen, 1987;Fouad, Hansen, &Arias, 1986Lonner, 1968;Lonner &Adams, 1972;Shah, 1971;Strong, 1943). However, Fouad (1993) discussed concerns with translation and international use, echoing Strong's (1943) concern that words may carry different meanings and occupations may not be the same in different countries.…”
Section: Cultural Influences On Vocational Interestsmentioning
confidence: 99%